1996
DOI: 10.1021/jm9604179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Bis-Intercalated Complexes of Ditercalinium and Flexi-Di with the Hexanucleotide d(GCGCGC)2:  Theoretical Analysis of the Interaction and Rationale for the Sequence Binding Specificity

Abstract: The X-ray crystal structures of the complexes of ditercalinium and Flexi-Di with d(CGCG) 2 have been studied by computational chemistry methods in an attempt to rationalize their distinct structural features. In addition, the complexes of these two bisintercalating drugs with d(GCGCGC) 2 have been modeled and subjected to 0.5 ns of molecular dynamics simulations in explicit solvent with the aim of evaluating the relative importance of hydrogen bonding and stacking interactions in the sequence binding specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
0
15
0
1
Order By: Relevance
“…[7] It has also been suggested that ditercalinium can recognize and stabilize the A-type DNA conformation adopted by d(GCGCGC) 2 . [8] Therefore, it may be that ditercalinium should be considered a structure-selective rather than a sequence-selective DNA binding agent. This consideration prompted us to examine the structural specificity of the drug by using the competition dialysis method.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It has also been suggested that ditercalinium can recognize and stabilize the A-type DNA conformation adopted by d(GCGCGC) 2 . [8] Therefore, it may be that ditercalinium should be considered a structure-selective rather than a sequence-selective DNA binding agent. This consideration prompted us to examine the structural specificity of the drug by using the competition dialysis method.…”
Section: Introductionmentioning
confidence: 99%
“…For example we hypothesized that specific hydrogen bonding and electrostatic interactions of the linker with the floor of the major groove contribute to groove reversal. However Gago and coworkers [25] discount the importance of these hydrogen bonding interactions in water. They argue for the importance of stacking interactions in groove reversal.…”
mentioning
confidence: 99%
“…It is also estimated that 74% of the 119 currently most important drugs contain active ingredients from plants used in traditional medicine for health care [12], these traditional medicines are primarily plant-based [13]. Another study of the most prescribed drugs in the USA indicated that a majority contained either a natural product or a natural product was used in the synthesis or design of the drug [14].…”
Section: Introductionmentioning
confidence: 99%